Terbinafine in acrylic polymer for the treatment of onychomycosis in hemodialysis patients: a phase II clinical trial - Bersano, Jeanne Marie Queiroz Borges; Cordeiro, Matheus Gobbo; Sciani, Juliana Mozer; Tescarollo, Iara Lúcia; Marson, Fernando Augusto Lima (Frontiers in Medicine, 2024)
Introduction Onychomycosis is a nail infection caused by dermatophyte fungi, non-dermatophyte fungi, and yeast. Patients with chronic kidney disease on dialysis are part of the population that presents higher rates of this disease, mainly due to immunosuppression. Among patients with chronic kidney disease on dialysis, the treatment of onychomycosis is complex, mainly due to the limitations imposed by comorbidities. In this context, the study evaluated the safety and potential efficacy of a treatment that combines nail debridement with the use of acrylic gel nails carrying terbinafine at a concentration of 2%. Methods Patients from the Hemodialysis Center of the São Francisco de Assis University Hospital in Bragança Paulista, São Paulo, Brazil were included. Those had hallux onychomycosis with clinical forms whose treatment involved the need for nail debridement. After the debridement procedure, a nail prosthesis made with acrylic reconstruction gel and 2% terbinafine was applied. The procedure was renewed every 2 weeks (~14 days) for 11 months. The evolution was monitored with measurements of the normal-appearing nail plate and photographs. Direct mycological examination and fungal culture were performed at the beginning of the study and 30 days after applications were interrupted. Assessment of clinical response, clinical cure, mycological cure, and complete cure was performed at the end of the study. All participants answered a questionnaire about their perception of the treatment. Results Out of the 155 patients on hemodialysis, 64/155 (41.3%) individuals were identified with symptoms suggestive of onychomycosis in the halluces after clinical analysis. Among them, 35/64 (54.7%) individuals presented a positive direct mycological examination and underwent fungal culture to identify the etiological agent. In this group of patients, 24/35 (68.6%) individuals who presented clinical forms whose treatment involved the need for nail debridement were selected. Only 15/24 (62.5%) individuals completed the study. Among the study participants, 5/15 (33.3%) still presented positive fungal culture in the presence of a negative direct mycological examination and 1/15 (6.7%) presented a positive direct mycological examination, but with a negative culture. Among those with a positive fungal culture, 3/15 (20.0%) participants presented microorganisms different from those isolated in the initial exams. Regarding cure, 5/15 (33.3%) participants showed a clinical response, 4/15 (26.7%) clinical cure, and 3/15 (20.0%) complete cure. No patient presented an allergic reaction or local irritation caused by the material used in the treatment. There were accidental superficial ulcerations caused by the electric sandpaper; however, no wound developed secondary infection. No participant reported discomfort due to the nail prosthesis use, 3/15 (20.0%) reported a feeling of discomfort caused by the vibration of the electric file and 12/15 (80.0%) reported the perception that their nails had a better appearance during treatment with nail prosthesis made with acrylic reconstruction gel and 2% terbinafine. Conclusion The application of 2% terbinafine in acrylic reconstruction gel for the manufacture of nail prostheses applied after debridement of moderate and severe forms of onychomycosis showed low efficacy as an isolated treatment in patients on dialysis due to chronic kidney disease. On the other hand, most patients had a good perception of the appearance of their nails during treatment, even when it did not result in apparent clinical improvement or complete cure.